2009
DOI: 10.1152/ajprenal.00270.2009
|View full text |Cite
|
Sign up to set email alerts
|

Akt1 mediates purinergic-dependent NOS3 activation in thick ascending limbs

Abstract: Silva GB, Garvin JL. Akt1 mediates purinergic-dependent NOS3 activation in thick ascending limbs. Am J Physiol Renal Physiol 297: F646 -F652, 2009. First published July 1, 2009 doi:10.1152/ajprenal.00270.2009.-Extracellular ATP regulates many physiological processes via release of nitric oxide (NO). ATP stimulates NO in thick ascending limbs (TALs), but the signaling cascade involved in the cells of this nephron segment, as well as many other types of cells, is poorly understood. We hypothesized that ATP enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…The fact that phosphoserine 1177 remained elevated at 10 min, whereas phosphoserine 633 was already back to basal levels, may indicate that phosphorylation at serine 633 is required during early stages of the signaling event. The fact that Ang II enhances phosphorylation of NOS3 at positive regulatory sites in conjunction with our previous data (16,28), indicate that NOS3 is the NOS isoform activated by Ang II.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The fact that phosphoserine 1177 remained elevated at 10 min, whereas phosphoserine 633 was already back to basal levels, may indicate that phosphorylation at serine 633 is required during early stages of the signaling event. The fact that Ang II enhances phosphorylation of NOS3 at positive regulatory sites in conjunction with our previous data (16,28), indicate that NOS3 is the NOS isoform activated by Ang II.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, luminal flow activates the PI3K/Akt path- way, stimulating NO production in isolated TALs (27). More recently, it has been reported that ATP stimulates TAL NO production upon activation of Akt1 (28). From these studies and the current work, we concluded that Akt1 is the primary mechanism by which Ang II activates NOS3 to stimulate NO production in the TAL.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…AQP1, AQP2, AQP3, AQP4 Aquaporin water channel isoforms (reproduced from [189] with permission from Springer) it was argued that the response was mediated primarily by P2X receptors. Further studies from the same group have defined NOS3 (eNOS) as the target for P2 receptor activation [338], in a process requiring activation of Akt1 (serine threonine kinase; aka PKB).…”
Section: Renal Tubulesmentioning
confidence: 99%
“…Separate TAL suspensions from the adenovirus-injected left kidney and noninjected right kidney were prepared as described previously (79). Total RNA was isolated from the suspensions using an RNeasy Plus mini kit (Qiagen, Valencia, CA) and subsequently used for RT-PCR analysis using a OneStep RT-PCR kit (Qiagen) according to the manufacturer's instructions.…”
Section: Nox4 Short Hairpin Rnamentioning
confidence: 99%